A instituição da supervisão de ensino e a municipalização em Valinhos : tensões, conflitos e incertezas - Macedo, Marina Quintanilha (Universidade Federal de São Carlos, 2008)
This dissertation analyses the establishment of the educational supervision in Valinhos municipality, after the municipalization, presenting the tensions and conflicts that this process raised, made explicit by the lack of knowledge of the School Supervisor s hole, demonstrating the existence of a confrontation between a traditional and patrimonialist administrative organization, based on a system of values and beliefs and the new rational institutional structure proposed by the State, through the municipalization of the education. This study used the theory developed by Max Weber related to the role of the technical and substantive rationality in the constitution of the western capitalism and the Modern State. The concepts and categories concerning the administrative rationalism and the forms of organization and development of the administrative structure are fundamental to the development of this research. At this point, we are particularly interested in the development of the function and post of the supervisor and the concepts of patrimonialism and bureaucratic organization.
Keywords: Supervisão escolar; Municipalização; Patrimonialismo; Educational supervision; Municipalization; CIENCIAS HUMANAS::EDUCACAO